Effect of gold nanoparticle in hole‐transport layer on inverted organic thin‐film solar cell performance. Issue 7 (28th April 2014) - Akiyama, Tsuyoshi; Nishida, Takuji; Matsumoto, Taisuke; Sakaguchi, Hiroshi; Suzuki, Atsushi; Oku, Takeo
<x xml:space="preserve">Abstract</x> Inverted‐type bulk‐heterojunction organic thin‐film solar cells with incorporated gold nanoparticles were fabricated and evaluated. Gold nanoparticles were incorporated into the hole‐transport layer, and subsequently positioned behind the photoactive layer, away from the light‐facing side of the solar cell. Incorporation of gold nanoparticles was confirmed by scanning electro microscopy, atomic force microscopy, and transmission absorption spectra. The incorporation of the gold nanoparticles improved the performance of the photovoltaic device, even gold nanoparticles were aggregated in the hole‐transport layer.